Seated versus standing cycling in competitive road cyclists: uphill climbing and maximal oxygen uptake - Tanaka, H.; Bassett, D. R.; Best, S. K.; Baker, K. R. (Canadian Journal of Applied Physiology, 1996)
Seven competitive road cyclists (M +/- SE = 23.7 +/- 1.5 yr, 70.5 +/- 1.7 kg) participated to determine the effects of cycling body position on physiological responses during uphill cycling and maximal oxygen uptake (VO2max). There was no significant difference in VO2max between seated and standing positions on a cycle ergometer (66.4 +/- 1.6 vs. 66.4 +/- 1.7 ml . kg-1 . min-1). When the subjects rode their own bicycle on a treadmill, oxygen uptake and heart rate were significantly (p < 0.05) higher during standing when subjects bicycled at 20.0 km . h-1 (4% grade), but no difference was observed when riding at 12.3 km . h-1 (10% grade). Leg RPE was significantly (p < 0.05) lower for standing position up a 10% grade. The results suggest that the standing position is less economical during moderate hill climbing, but during steep hill climbing, it results in a decreased sensation of effort in the legs.